P810 Clinical features of ulcerative colitis patients in Sardinia, Italy – First results from a multi-centre study. (25th January 2019) - Mocci, G; Demurtas, M; Onidi, F M; Manca, R; Miculan, F; Dore, M P; Quarta Colosso, B; Cicu, A; Cugia, L; Pisanu, R; Carta, M; Binaghi, L; et al.
Abstract: Background: There are few data on epidemiological and clinical features of adult ulcerative colitis (UC) patients in Sardinia (Italy), mainly derived from administrative sources such as Hospital Discharge Register. The aim of this study was to assess the main clinical and epidemiological features of adult patients diagnosed with ulcerative colitis (UC) in Sardinia, Italy. Methods: We evaluated the main clinical features of UC patients followed-up in 7 Gastroenterology/Endoscopy Units in Sardinia, Italy. Data were obtained from medical patients' records and from a questionnaire administered at inclusion visit. Results: 374 patients with UC were included: 52.9% were female, with a female-to-male ratio of 1.125. Eleven per cent of patients were active smokers and 36.4% were former smokers. Mean age at diagnosis was 39.2 years (SD 15.4). Only 4.3% of patients were < 16 years old at diagnosis; 53.2% were diagnosed at age ranging from 17 to 40 and 42.5% at age >40. About three quarters of patients were diagnosed between 17 and 49 years old (23.7% between 17 and 29, 25.8% between 30 and 39 and 22.8% between 40 and 49). Disease extent at diagnosis was proctitis in 18.2% of patients, left-sided colitis in 38.8% and extensive colitis in 41.2% (missing data in 1.9% of patients). After a median disease duration of 9 years (IQR 13.8), proximal extension of proctitis or left-sided colitis (from E1 to E2/E3 or from E2 to E3) occurred in 12% of patients. 17.9% of patients developed extraintestinal manifestations, the most frequent being articular (11.8%). There were six patients (1.6%) with concomitant primary sclerosing cholangitis. Two patients developed colorectal cancer. Conclusions: This multi-centre study provides important preliminary clinical data on UC in Sardinia.